Reticulate Acropigmentation of Kitamura: A rare hyperpigmented genetic skin disorder (Indian Journal of Case Reports, 2026)
Reticulate acropigmentation of Kitamura is an exceptionally rare autosomal dominant genodermatosis characterized by reticulate hyperpigmented macules that interrupt the dermatoglyphics, primarily affecting the dorsa of the hands and feet. We report a case of a 65-year-old man who presented with multiple bilateral symmetrical, hyperpigmented, well-defined, discrete macules and plaques over the neck, both shoulders, both axillae, both cubital fossae, both knees, both legs, and the bilateral dorsa of the hands, present for approximately 1½ months with recent progression over the preceding 15 days. A positive family history in the patient’s brother supported the autosomal dominant inheritance pattern. Skin biopsy confirmed the diagnosis, demonstrating hyperkeratosis, irregular acanthosis, filiform elongation of rete ridges, and increased melanocytes within the elongated epidermal projections. The importance of clinicopathological correlation in achieving an accurate diagnosis of this rare pigmentary disorder is emphasized.